Cobalt-aluminum-titanium co-coated positive electrode material as well as preparation method and application thereof
By forming a cobalt, aluminum, and titanium co-clad layer on the surface of the positive electrode material, the problems of high charge transfer impedance and insufficient gas production in the high temperature and height disengagement state of the existing positive electrode material are solved, and a positive electrode material with low impedance and stable surface structure is achieved.
Patent Information
- Application Number
- CN202510362024.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
It is difficult for existing positive electrode materials to effectively reduce charge transfer impedance in high temperature and high disengagement states, and surface treatment measures are insufficient to reduce gas production.
A co-coated positive electrode material is made of co-cobalt-aluminum-titanium, and a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is used as the core, and a cladding layer containing Co, Al and Ti elements is formed on its surface, and the element content and content relationship in the cladding layer are strictly controlled.
It realizes maintaining good rate performance at high voltage, reducing the charge transfer impedance of the positive electrode material, reducing battery gas production at high temperatures, and improving the surface structure stability of the material.
Smart Images

Figure CN119890277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a cobalt-aluminum-titanium co-coated positive electrode material, a preparation method and an application thereof. Background Art
[0002] Today, lithium-ion batteries are widely used in all walks of life as an environmentally friendly green energy source. High-rate tool electronic products have increasingly higher requirements for the safety characteristics of lithium-ion batteries in terms of electrical abuse and high temperature conditions. Considering the actual application scenarios of rate-type cylindrical cells, it is required that when the cells are charged and discharged at high temperatures (such as 45°C or 60°C), they will not fail within the specified number of cycles due to gas production triggering the current interrupt device (CID); and the cells are also required not to catch fire or explode during the process of constant current charging from the open circuit voltage to the cut-off voltage (exceeding the normal application upper limit voltage, such as 5V).
[0003] In order to meet the needs of customers, the positive electrode material, which is an important component of the battery cell, is required to have high-valent Ni that does not react with the electrolyte and no interlayer separation occur inside the primary grains under conditions of high lithium depletion and high temperature; it is also required that the primary grains do not separate and more seriously collapse under conditions of drastic changes in the structural volume.
[0004] At present, in order to meet the above requirements, the positive electrode material will be surface treated, including optimization by coating elements (such as Al, Co, B, etc.) to enhance the adhesion between the surface grain boundaries or stabilize the oxygen atoms in the lattice. It also includes adding a water washing step to reduce the residual alkali on the surface of the material and form a passivation layer. However, the above measures will significantly deteriorate the surface charge transfer impedance, increase the lithium ion deintercalation energy barrier, and further deteriorate the direct current internal resistance (DCR) of the battery cell, affecting its battery cell cycle, high rate discharge and other performance; moreover, the above measures are not effective enough to reduce gas production under high temperature and high detachment conditions.
[0005] Therefore, how to enhance the surface of the positive electrode material, reduce gas production and effectively reduce the charge transfer impedance of the positive electrode is a technical problem that needs to be solved at present. Summary of the invention
[0006] In view of the above-mentioned technical problems existing in the prior art, the object of the present invention is to provide a cobalt-aluminum-titanium co-coated positive electrode material and a preparation method and application thereof.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a cobalt-aluminum-titanium co-coated positive electrode material, wherein the cobalt-aluminum-titanium co-coated positive electrode material comprises a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, wherein the chemical composition of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
[0009] The surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is provided with a coating layer, and the coating layer contains Co, Al and Ti elements. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the contents of Co, Al and Ti in the coating layer satisfy:
[0010] The content ω1 of the Co element is 500ppm~8000ppm; the content ω2 of the Al element is 500ppm~6000ppm; the content ω3 of the Ti element is 0ppm~1500ppm and does not contain 0ppm; ω1+ω2 is 1500ppm~12000ppm; among which, ω1+ω2≥ω3.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, (ω1+ω2) / ω3≥2, preferably (ω1+ω2) / ω3≥3, and more preferably 4≤(ω1+ω2) / ω3≤20.
[0013] Preferably, ω1 is 1000ppm~8000ppm.
[0014] Preferably, ω2 is 1000ppm~4000ppm.
[0015] Preferably, ω3 is 1000ppm~1500ppm.
[0016] Preferably, the content of Co in the coating layer is greater than the content of Al in the coating layer, or the ratio of the content of Al in the coating layer to the content of Co in the coating layer is 1 to 1.2, or the content of Al in the coating layer is 300 ppm to 600 ppm more than the content of Co in the coating layer. Preferably, in the coating layer, Co, Al and Ti exist in the form of one or more compounds, and the total mass of the compounds accounts for more than 80% of the total mass of the coating layer, preferably more than 90%.
[0017] In a second aspect, the present invention provides a method for preparing the cobalt-aluminum-titanium co-coated positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) Mixing nickel-cobalt hydroxide, a doping source and a lithium source and sintering them to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material;
[0019] Wherein, the doping elements in the doping source include Al element and A element, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti;
[0020] (2) mixing a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a coating material and sintering the mixture to obtain the cobalt-aluminum-titanium co-coated positive electrode material;
[0021] Wherein, the coating material includes Co source, Al source and Ti source.
[0022] Preferably, in step (1), the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05.
[0023] Preferably, in step (1), the sintering temperature is 400°C to 1000°C.
[0024] Preferably, in step (1), the sintering time is 6 h to 20 h.
[0025] Preferably, in step (2), the Co source includes at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide.
[0026] Preferably, in step (2), the Al source includes at least one of aluminum oxide, aluminum hydroxide and aluminum oxyhydroxide.
[0027] Preferably, in step (2), the Ti source is titanium oxide.
[0028] Preferably, the titanium oxide includes at least one of titanium dioxide, titanium monoxide, titanium trioxide and titanium tetraoxide.
[0029] Preferably, in step (2), the sintering temperature is 350°C to 800°C.
[0030] Preferably, in step (2), the sintering time is 8 h to 24 h.
[0031] Preferably, in step (2), after the sintering is completed, the temperature is cooled at a cooling rate of 0.01°C / min to 3°C / min.
[0032] As a preferred technical solution of the preparation method of the present invention, the method further comprises: washing the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material prepared in step (1) with water, and then mixing it with a Co source, an Al source and a Ti source and sintering it to prepare a cobalt-aluminum-titanium co-coated positive electrode material.
[0033] As another preferred technical solution of the preparation method of the present invention, step (2) comprises: mixing the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a portion of the coating material and sintering it once, washing the product of the primary sintering with water, and then mixing it with another portion of the coating material and sintering it twice to obtain the cobalt-aluminum-titanium co-coated positive electrode material.
[0034] Preferably, the temperature of the primary sintering and the secondary sintering are independently 350° C. to 800° C. Here, “independently” means that the temperature of the primary sintering and the secondary sintering can be the same or different, and the two are independent of each other.
[0035] Preferably, the total time of the primary sintering and the secondary sintering is 8 h to 24 h.
[0036] In a third aspect, the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode comprises the cobalt-aluminum-titanium co-coated positive electrode material described in the first aspect.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The positive electrode material of the present invention uses a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material as its core, and has good rate performance under high voltage; further, on the basis of Al element and / or Co element coating, Ti element co-coating is added, and the contents and content relationship of Co element, Al element, and Ti element are strictly controlled, so that a positive electrode material with low impedance and stable surface structure can be obtained, thereby reducing battery gas production under high temperature.
[0039] Compared with the positive electrode material coated with Al element and / or Co element, the positive electrode material of the present invention has a charge transfer impedance per unit area of the prepared positive electrode sheet reduced by 15% to 30%, and when applied to 18650 cylindrical battery cells, the DCR is reduced by 0.5 mΩ to 1 mΩ, the gas production is reduced by 10% to 30% after 400 cycles at 45°C, and the gas production is reduced by 30% to 50% when fully charged at 70°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope image of the cobalt-aluminum-titanium co-coated positive electrode material of Example 1.
[0041] Figure 2 It is an XRD comparison diagram of the cobalt-aluminum-titanium co-coated positive electrode material of Example 1 and the cobalt-aluminum co-coated positive electrode material of Comparative Example 1. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0043] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] In one embodiment of the present invention, a cobalt-aluminum-titanium co-coated positive electrode material is provided, wherein the cobalt-aluminum-titanium co-coated positive electrode material comprises a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, wherein the chemical composition of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
[0045] The surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is provided with a coating layer, and the coating layer contains Co, Al and Ti elements. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the contents of Co, Al and Ti in the coating layer satisfy:
[0046] The content ω1 of the Co element is 500ppm~8000ppm; the content ω2 of the Al element is 500ppm~6000ppm; the content ω3 of the Ti element is 0ppm~1500ppm and does not contain 0ppm; ω1+ω2 is 1500ppm~12000ppm; among which, ω1+ω2≥ω3.
[0047] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, the chemical composition of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
[0048] Exemplarily, 1≤α≤1.05, for example, it can be 1, 1.01, 1.02, 1.03, 1.04 or 1.05, etc.; 0.80≤x≤0.95, for example, it can be 0.80, 0.82, 0.83, 0.85, 0.88, 0.89, 0.90, 0.92, 0.93, 0.94 or 0.95, etc.; 0.04≤y≤0.15, for example, it can be 0.04, 0.06, 0.08 , 0.10, 0.12, 0.13, 0.14 or 0.15, etc.; 0.005≤z≤0.06, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05 or 0.06, etc.; 0≤m≤0.02, for example, it can be 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.01, 0.012, 0.015, 0.017 or 0.02, etc. Wherein, when m is 0, it means that the chemical composition does not contain element A.
[0049] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, the content ω1 of the Co element in the coating layer is 500ppm~8000ppm, for example, it can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1700ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2500ppm, 2650ppm, 2800ppm, 3000ppm, 3200ppm, 3300ppm, 3500ppm , 3700ppm, 3800ppm, 4000ppm, 4200ppm, 4400ppm, 4500ppm, 4700ppm, 4800ppm, 5000ppm, 5200ppm, 5500ppm, 5600ppm, 5800ppm, 6000ppm, 6200ppm, 6300ppm, 6400ppm, 6500ppm, 6700ppm, 6800ppm, 7000ppm, 7200ppm, 7400ppm, 7600ppm, 7800ppm or 8000ppm, and more preferably 1000ppm to 8000ppm. If the content of Co is too low, the total content of Co and Al will decrease, and the insufficient coating amount will make them insufficient for interface protection, and the impedance will not be improved, that is, the impedance and interface improvement will deteriorate. If the Co content is too high, when the Co content is greater than 8000ppm, most of the final Co compounds are converted into LiCoO2, which leads to a substantial increase in LiCoO2. This substance is unstable under high temperature and high voltage and is prone to explosion. Therefore, the product design of the present invention needs to strictly restrict the Co content, which must not exceed 8000ppm.
[0050] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, the content of Al element in the coating layer ω2 is 500ppm~6000ppm, for example, it can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1700ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2500ppm ppm, 1500ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3500ppm, 3700ppm, 3800ppm, 4000ppm, 4200ppm, 4400ppm, 4500ppm, 4700ppm, 4800ppm, 5000ppm, 5200ppm, 5500ppm, 5600ppm, 5800ppm or 6000ppm, etc., preferably 1000ppm ~ 4000ppm.
[0051] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, the content ω3 of the Ti element in the coating layer is 0ppm~1500ppm and does not contain 0ppm, for example, it can be 0.01ppm, 0.05ppm, 0.1ppm, 0.5ppm, 1ppm, 3ppm, 5ppm, 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 60ppm, 70ppm, 80ppm 0ppm, 100ppm, 120ppm, 150ppm, 170ppm, 185ppm, 200ppm, 230ppm, 260ppm, 280ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm or 1500ppm, etc. If the content ω3 of the Ti element exceeds 1500ppm, it will significantly affect the discharge capacity of the positive electrode material; if the Ti element is not added, it will not be able to synergize with the Co element and the Al element to achieve the effect of reducing impedance. When the coating amount is less than 50ppm and greater than 0ppm, the effect of reducing impedance will be a little worse, but the technical effect of the present invention can still be achieved, so the content ω3 of the Ti element is preferably: ω3≥50ppm.
[0052] In one embodiment, ω3 is 1000 ppm to 1500 ppm.
[0053] In one embodiment of the present invention, by limiting the content of cobalt element to 1000ppm~8000ppm and the content of Ti element to 1000ppm~1500ppm, it is more conducive to forming a fast ion conductor during the sintering process (especially at a higher sintering temperature), thereby improving the performance of the positive electrode material.
[0054] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, ω1+ω2 is 1500ppm~12000ppm, for example, it can be 1500ppm, 1700ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2500ppm, 2650ppm, 2800ppm, 3000ppm, 3200ppm, 3300ppm, 3500ppm, 3700ppm, 3800ppm, 4000ppm, 4200ppm ppm、4400ppm、4500ppm、4700ppm、4800ppm、5000ppm、5200ppm、5500ppm、5600ppm、5800ppm、6000ppm、6500ppm、7 000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, 10500ppm, 11000ppm, 11500ppm or 12000ppm, etc.
[0055] In one embodiment of the present invention, since (ω1+ω2) / ω3≥1, the content of each of the Co element and the Al element is within a specific range, wherein the introduction of Ti can significantly reduce the impedance of the battery cell, and significantly reduce the gas production during high temperature storage and high temperature cycling, but if the content of Ti is too high, it will significantly deteriorate the gram capacity of the positive electrode material, therefore, the coating content of Ti must be limited. The present invention controls the content of Ti to be less than or equal to the sum of the contents of Co and Al, and controls the content of the Ti element, so that the gram capacity of the positive electrode material will not deteriorate, while also being able to ensure the effect of Co and Al coating, while also being able to achieve the technical effect of ensuring the integrity of the interface coating and reducing high temperature gas production.
[0056] In the positive electrode material of the present invention, the Al element in the coating layer and the Co element in the coating layer do not strictly require that the Co content must be greater than the Al content. If there are only two coating elements, Co and Al, in the coating layer, the presence of Al will greatly reduce the impedance of the battery cell. At this time, in order to take into account the overall impedance and overcharge gas production performance of the battery cell, the Al content must in principle be less than the Co content.
[0057] However, in the present invention, since Ti is introduced into the coating layer, it can significantly reduce the impedance of the battery cell. Therefore, the introduction of Ti can increase the tolerance to the Al element, and the introduction of Ti can offset the impedance increase caused by the increase of the Al element, so that the maximum content of Al can also slightly exceed Co. For example, in one embodiment, the ratio of the content of the Al element in the coating layer to the content of the Co element in the coating layer is 1 to 1.2, for example, it can be 1, 1.05, 1.1, 1.15 or 1.2, etc.; in another embodiment, the content of the Co element in the coating layer is greater than the content of the Al element in the coating layer; in another embodiment, the content of the Al element in the coating layer is 300ppm to 600ppm more than the content of the Co element in the coating layer, for example, it can be 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 550ppm or 600ppm, etc.
[0058] As a preferred solution, the content of the Co element in the coating layer is greater than the content of the Al element in the coating layer, that is, ω1>ω2.
[0059] The positive electrode material of one embodiment of the present invention uses a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material as the core, which has good rate performance under high voltage; further, on the basis of Al element and / or Co element coating, Ti element co-coating is added, and the content and content relationship of Co element, Al element, and Ti element are strictly controlled, so as to obtain a positive electrode material with low impedance and stable surface structure.
[0060] The positive electrode material of one embodiment of the present invention has a charge transfer impedance per unit area of the prepared positive electrode sheet reduced by 15% to 30% compared with the positive electrode material coated with Al element and / or Co element, and when applied to 18650 cylindrical battery cells, the DCR is reduced by 0.5mΩ to 1mΩ, the gas production is reduced by 10% to 30% after 400 cycles at 45°C, and the gas production is reduced by 30% to 50% when fully charged at 70°C.
[0061] In the cobalt-aluminum-titanium co-coated positive electrode material provided in one embodiment of the present invention, (ω1+ω2) / ω3≥2, illustratively, (ω1+ω2) / ω3 can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, 20, 20.5, 21, 21.5, 22, 22.5, 23, 23.5, 24, 24.5 or 25, etc. In one embodiment, (ω1+ω2) / ω3≥3.
[0062] In one embodiment, 4≤(ω1+ω2) / ω3≤20.
[0063] In one embodiment, ω1 is 1000 ppm to 8000 ppm.
[0064] In one embodiment, ω2 is 1000 ppm to 4000 ppm.
[0065] In one embodiment, in the coating layer, the Co element, the Al element and the Ti element exist in the form of one or more compounds, and the total mass of the compounds accounts for more than 80% of the total mass of the coating layer, for example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, etc., preferably more than 90%, more preferably more than 95%.
[0066] In another embodiment, the present invention provides a method for preparing the cobalt-aluminum-titanium co-coated positive electrode material as described above, the preparation method comprising the following steps:
[0067] (1) Mixing nickel-cobalt hydroxide, a doping source and a lithium source and sintering them to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material;
[0068] Wherein, the doping elements in the doping source include Al element and A element, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti;
[0069] (2) mixing a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a coating material and sintering the mixture to obtain the cobalt-aluminum-titanium co-coated positive electrode material;
[0070] Wherein, the coating material includes Co source, Al source and Ti source.
[0071] This scheme is a more preferred secondary dry sintering preparation method of the present invention. The secondary dry sintering preparation method can enhance the surface of the positive electrode material, reduce gas production and effectively reduce the charge transfer impedance of the positive electrode.
[0072] In the preparation method of the cobalt-aluminum-titanium co-coated positive electrode material provided by one embodiment of the present invention, the Co source and Ti source in the coating material react with the residual lithium on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material to partially generate a fast ion conductor. In particular, the introduction of the Ti source can significantly reduce the surface impedance of the material and has no significant effect on the cycle performance. At the same time, the Al source in the coating material will form an inert layer, which can significantly improve the impedance to a certain extent, but can significantly improve the cycle performance and curb gas production.
[0073] In one embodiment, in step (1), the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05, for example, 1, 1.01, 1.02, 1.03, 1.04 or 1.05.
[0074] In one embodiment, in step (1), the sintering temperature is 400°C to 1000°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C.
[0075] In one embodiment, in step (1), the sintering time is 6 h to 20 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.
[0076] In one embodiment, in step (2), the Co source includes at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide.
[0077] In one embodiment, in step (2), the Al source includes at least one of aluminum oxide, aluminum hydroxide and aluminum oxyhydroxide.
[0078] In one embodiment, in step (2), the Ti source is titanium oxide.
[0079] In one embodiment, the titanium oxide includes at least one of titanium dioxide, titanium monoxide, titanium trioxide and titanium tetraoxide, but is not limited to the above-mentioned types, and other titanium oxides commonly used in the art are also applicable to the present invention.
[0080] In one embodiment, in step (2), the sintering temperature is 350°C to 800°C, for example, it can be 350°C, 370°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C.
[0081] In one embodiment, in step (2), the sintering time is 8 h to 24 h, for example, it can be 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 22 h or 24 h.
[0082] In one embodiment, in step (2), after the sintering is completed, the temperature is cooled at a cooling rate of 0.01°C / min to 3°C / min. For example, the cooling rate may be 0.01°C / min, 0.05°C / min, 0.1°C / min, 0.2°C / min, 0.5°C / min, 0.7°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, etc.
[0083] In one embodiment, the method further comprises: washing the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material prepared in step (1), and then mixing it with a Co source, an Al source, and a Ti source and sintering it to prepare a cobalt-aluminum-titanium co-coated positive electrode material. By adding a water washing step, the residual alkali on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material obtained by sintering can be reduced.
[0084] In one embodiment, step (2) comprises: mixing a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a portion of a coating material and performing a primary sintering, washing the product of the primary sintering with water, and then mixing it with another portion of the coating material and performing a secondary sintering to obtain the cobalt-aluminum-titanium co-coated positive electrode material.
[0085] Water washing can reduce residual alkali on the surface and reduce gas production during circulation and high-temperature storage.
[0086] In one embodiment, the temperature of the primary sintering and the secondary sintering is independently 350°C to 800°C, for example, 350°C, 370°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc. "Independently" means that the temperature of the primary sintering and the secondary sintering can be the same or different, and the two are independent of each other.
[0087] In one embodiment, the total time of the primary sintering and the secondary sintering is 8 h to 24 h, for example, it can be 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 22 h or 24 h.
[0088] In another embodiment, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode comprises the cobalt-aluminum-titanium co-coated positive electrode material described in the first aspect.
[0089] The following are typical but non-limiting examples:
[0090] Example 1
[0091] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0092] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0093] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0094] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.03, the sintering temperature is 710°C, and the sintering time is 18 hours.
[0095] Step 2: Coating process:
[0096] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 500°C, and the sintering time is 10h.
[0097] Figure 1 This is a scanning electron microscope image of the cobalt-aluminum-titanium co-coated positive electrode material of this embodiment. It can be seen from the image that the material is coated evenly, with no coating residue and no fine powder.
[0098] Example 2
[0099] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0100] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0101] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0102] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is Li2CO3, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 720°C, and the sintering time is 19 hours.
[0103] Step 2: Coating process:
[0104] After the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, a secondary sintering is carried out in an oxygen atmosphere, and the temperature is cooled to room temperature at a cooling rate of 0.5°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum hydroxide and titanium monoxide, the sintering temperature is 600°C, and the sintering time is 13h.
[0105] Example 3
[0106] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0107] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0108] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0109] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.05, the sintering temperature is 695°C, and the sintering time is 14 hours.
[0110] Step 2: Coating process:
[0111] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 0.8°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum hydroxide and titanium trioxide, the sintering temperature is 650°C, and the sintering time is 9h.
[0112] Example 4
[0113] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0114] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0115] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0116] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.01, the sintering temperature is 690°C, and the sintering time is 15 hours.
[0117] Step 2: Coating process:
[0118] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1.5°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 680°C, and the sintering time is 12h.
[0119] Example 5
[0120] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0121] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0122] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0123] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.04, the sintering temperature is 650°C, and the sintering time is 12 hours.
[0124] Step 2: Coating process:
[0125] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 580°C, and the sintering time is 10 hours.
[0126] Example 6
[0127] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0128] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0129] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0130] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 670°C, and the sintering time is 14 hours.
[0131] Step 2: Coating process:
[0132] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an oxygen atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 560°C, and the sintering time is 10 hours.
[0133] Example 7
[0134] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0135] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0136] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0137] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 720°C, and the sintering time is 14 hours.
[0138] Step 2: Coating process:
[0139] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 700°C, and the sintering time is 10h.
[0140] Example 8
[0141] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0142] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0143] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0144] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is alumina, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 720°C, and the sintering time is 14 hours.
[0145] Step 2: Coating process:
[0146] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 700°C, and the sintering time is 10h.
[0147] Example 9
[0148] The present embodiment provides a cobalt-aluminum-titanium co-coated positive electrode material, which includes a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material (see Table 1 for the chemical formula); a coating layer is provided on the surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and the coating layer contains Co element, Al element and Ti element. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the content of Co element ω1, the content of Al element ω2, the content of Ti element ω3, the sum of the contents of Co element and Al element ω1+ω2, and the ratio of the sum of the contents of Co element and Al element to the content of Ti element (ω1+ω2) / ω3 in the coating layer are shown in Table 2.
[0149] This embodiment also provides a method for preparing the above-mentioned cobalt-aluminum-titanium co-coated positive electrode material, comprising the following steps:
[0150] Step 1: Preparation of high-nickel nickel-cobalt-aluminum-based ternary cathode material:
[0151] After mixing and grinding nickel cobalt hydroxide, a doping source and a lithium source, sintering is performed once to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; wherein the doping source is aluminum hydroxide, the lithium source is LiOH, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 720°C, and the sintering time is 14 hours.
[0152] Step 2: Coating process:
[0153] The high-nickel nickel-cobalt-aluminum-based ternary positive electrode material and the coating material are mixed and ground evenly, and then secondary sintering is carried out in an air atmosphere, and the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain the cobalt-aluminum-titanium co-coated positive electrode material; wherein the coating material is cobalt hydroxide, aluminum oxide and titanium dioxide, the sintering temperature is 700°C, and the sintering time is 10h.
[0154] Example 10
[0155] The difference between this embodiment and embodiment 1 is that the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material obtained in step 1 is washed with water and then used in step 2 for the coating process.
[0156] Embodiment 11
[0157] The difference between this embodiment and embodiment 1 is that step (2) includes:
[0158] A high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is mixed with 50wt% of a coating material and sintered once, the product of the primary sintering is washed with water, and then mixed with the remaining coating material and sintered twice to obtain the cobalt-aluminum-titanium co-coated positive electrode material. The atmosphere for the primary sintering and the secondary sintering are both air atmospheres, the temperature is both 500°C, the sintering time is both 5h, and the cooling rate after sintering is both 1°C / min.
[0159] Comparative Example 1
[0160] The difference from Example 1 is that titanium dioxide is removed from the coating material in step 2 to obtain a cobalt-aluminum co-coated positive electrode material, referred to as Li 1.03 (Ni 0.88 Co 0.10 Al 0.02 )O2@(CoAl), the element coating amounts in the coating layer are shown in Table 2.
[0161] Figure 2 It is an XRD comparison diagram of the cobalt-aluminum-titanium co-coated positive electrode material of Example 1 and the cobalt-aluminum co-coated positive electrode material of Comparative Example 1. It can be seen from the figure that Ti coating does not affect the crystal structure of the material.
[0162] Comparative Example 2
[0163] The difference from Example 1 is that the aluminum hydroxide is removed from the coating material in step 2 to obtain a cobalt-titanium co-coated positive electrode material, referred to as Li 1.03 (Ni 0.88 Co 0.10 Al 0.02 )O2@(CoTi), the element coating amounts in the coating layer are shown in Table 2.
[0164] Comparative Example 3
[0165] The difference from Example 1 is that the cobalt hydroxide is removed from the coating material in step 2 to obtain an aluminum-titanium co-coated positive electrode material, referred to as Li 1.03 (Ni 0.88 Co 0.10 Al 0.02 )O2@(AlTi) , the element coating amount in the coating layer is shown in Table 2.
[0166] Comparative Example 4
[0167] The difference from Example 1 is that the cobalt hydroxide and aluminum hydroxide are removed from the coating material in step 2 to obtain a titanium-coated positive electrode material, referred to as Li 1.03 (Ni 0.88 Co0.10 Al 0.02 )O2@(Ti) , the element coating amount in the coating layer is shown in Table 2.
[0168] Comparative Example 5
[0169] The difference from Example 1 is that the contents of Co and Al in the coating layer are both 500 ppm, and the content of Ti is 1500 ppm.
[0170] Table 1
[0171]
[0172] Table 2
[0173]
[0174] The positive electrode materials of Examples 1-9 and Comparative Examples 1-5 were used to prepare positive electrodes and assemble batteries. Specifically:
[0175] Prepare the battery:
[0176] (1) Preparation of positive electrode sheet:
[0177] The positive electrode materials of Examples 1-9 and Comparative Examples 1-5 were used as active materials, and the active materials were mixed with a conductive agent Super P and a binder PVDF in NMP at a mass ratio of 95:2:3 to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of an aluminum foil and dried to obtain a positive electrode sheet.
[0178] (2) Preparation of negative electrode sheet:
[0179] The artificial graphite negative electrode, the conductive agent Super P, the binder CMC, and the thickener SBR were mixed in water at a mass ratio of 96:0.5:1.5:2 to obtain a negative electrode slurry. The negative electrode slurry was coated on the surface of the copper foil and dried to obtain a negative electrode sheet.
[0180] (3) Providing a diaphragm and an electrolyte, wherein the diaphragm is a multilayer composite diaphragm, the substrate material is a polyolefin polymer, and the composite material is a high heat-resistant inorganic ceramic; the electrolyte is obtained by dissolving LiPF6 in a mixed solvent of EC, DMC and FEC, wherein the mass ratio of EC:DMC:FEC:LiPF6 is 20:60:5:15.
[0181] (4) After winding the above-mentioned positive electrode sheet, negative electrode sheet and separator, a cylindrical battery cell is obtained, and the cylindrical battery cell is placed in a battery case and injected with electrolyte to obtain an 18650 battery.
[0182] Performance Testing:
[0183] (1) Charge transfer resistance per unit area R of 50% SOC positive electrode ct Test: Disassemble the cylindrical battery cell with 50% SOC to obtain the positive electrode sheet, and then cut several positive electrode sheets. A symmetrical battery is composed of a positive electrode sheet, a separator and a positive electrode sheet. Then use the Blue Electric test system to perform AC impedance test, and finally get R in the AC impedance test data. ct data.
[0184] (2) DC internal resistance (DCR) test of 50% SOC 18650 battery: Use 50% SOC 18650 cylindrical battery cells without disassembly and directly perform DC impedance test on the Blue Electric test system to obtain the DC internal resistance.
[0185] (3) Under the conditions of 70°C and 100% SOC, the impedance before storage and after 30 days of storage was tested, and the gas production and impedance growth rate after 30 days of storage were calculated.
[0186] (4) Charge and discharge the 18650 battery at 45°C, 2C charging, 3C discharging, 400 cycles, record the gas production and calculate the capacity retention rate at 400 cycles.
[0187] The test results are shown in Table 3.
[0188] Table 3
[0189]
[0190] As shown in Table 3, the positive electrode material of the present invention has a higher charge transfer impedance per unit area R than the positive electrode material co-coated with cobalt and aluminum (Comparative Example 1). ct When applied to 18650 cylindrical cells, the DCR is reduced by 0.5 mΩ~1.0 mΩ; the gas production after 30 days of storage at 100% SOC 70℃ is reduced by 13.5~23.5%, and the impedance growth rate is reduced by 11.0%~18.5%; after 400 cycles at 45℃, the gas production is reduced by 22.0%~28.0%, and the capacity retention rate is increased by 4.0%~6.0%.
[0191] In particular, what needs to be explained about the value of "50% SOC DC internal resistance" is that since the positive electrode is only one component of the entire cylindrical battery cell, if this data increases by 0.5 mΩ, it means that it is a very large impedance increase, which will have a greater impact on the entire battery cell.
[0192] In Examples 6 and 7, the contents of Co and Ti are relatively high, and the secondary sintering temperature is relatively high, so they are more inclined to form low-impedance fast ion conductors. However, the content of Al in the coating layer of Example 7 is higher, so the optimal group in the impedance performance table is Example 6, and for the gas production performance, the optimal group is Example 7.
[0193] The coating layer of Comparative Example 1 lacks the Ti element, the coating layer of Comparative Example 3 lacks the Co element, and the coating amount of the Al element in Comparative Example 3 is the largest, and its impedance performance is the worst; the coating layers of Comparative Examples 2 and 4 both lack the Al element, and their cycle performance deteriorates, and the coating amount of the Ti element in the coating layer of Comparative Example 4 is larger, and its gas production is improved to a certain extent compared with Comparative Example 2, but both are much higher than the embodiments.
[0194] Although the coating layer of Comparative Example 5 contains Co, Al and Ti elements at the same time, the total coating amount of Co and Al elements is small, and the sum of the contents of Co and Al elements is less than the content of Ti. Although the charge transfer impedance per unit area of the positive electrode has not deteriorated significantly, the DCR after being made into 18650 battery cells is 21.5mΩ, which is also slightly increased. The gas production at 70°C full power storage is 15.73mL, and the impedance growth rate is 51.2%, which is quite obvious. After 400 cycles at 45°C, the gas production is 32.7mL, and the final cycle retention rate of 400 cycles is only 77.20%.
[0195] At the same time, we can see that although the content of Co+Al≥Ti is a basic requirement, it can be seen from Examples 1-9 that when actually designing the coating scheme, the content of Ti will be adjusted at any time with the change of Co+Al. In general, the content of Ti is positively correlated with the content of Co+Al.
[0196] A further preferred scheme is that (ω1+ω2) / ω3≥2, more preferably (ω1+ω2) / ω3≥3, and further preferably 4≤(ω1+ω2) / ω3≤20. Ti coating is a subordinate secondary coating element of Co and Al, and a supplement to the main coating elements Co and Al. At the same time, it supplements the performance and plays a role in further strengthening the Co+Al coating system.
[0197] When (ω1+ω2) / ω3≥2, the improvement of Co improves the gram capacity of the material, and the coating improves the gram capacity, but Ti and Al do not provide capacity improvement, and in essence, Ti is a modified component for the co-coating of Co and Al, which can alleviate the deterioration of impedance caused by Al, and further reduce the gas production of high-temperature storage and high-temperature cycling. If selected, when (ω1+ω2) / ω3≥2, relative to (ω1+ω2) / ω3≥1, its capacity loss is smaller.
[0198] When (ω1+ω2) / ω3≥3, similarly, this component can better take into account the material's gram capacity, material impedance, and high-temperature storage and high-temperature gas production performance. Similarly, we prefer 4≤(ω1+ω2) / ω3≤20.
[0199] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0200] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A cobalt-aluminum-titanium co-coated positive electrode material, characterized in that: The cobalt-aluminum-titanium co-coated positive electrode material comprises a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, wherein the chemical composition of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti; The surface of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material is provided with a coating layer, and the coating layer contains Co, Al and Ti elements. Based on the total mass of the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, the contents of Co, Al and Ti in the coating layer satisfy: The content of Co element ω1 is 500ppm~8000ppm; The content of Al element ω2 is 500ppm~6000ppm; The content of Ti element ω3 is 0ppm~1500ppm and does not contain 0ppm; ω1+ω2 is 1500ppm~12000ppm; Among them, ω1+ω2≥ω3.
2. The cobalt-aluminum-titanium co-coated positive electrode material according to claim 1, characterized in that: (ω1+ω2) / ω3≥2; and / or, ω1 is 1000ppm~8000ppm; and / or, ω2 is 1000ppm~4000ppm; and / or, ω3 is 1000ppm~1500ppm.
3. The cobalt-aluminum-titanium co-coated positive electrode material according to claim 2, characterized in that: 4≤(ω1+ω2) / ω3≤20.
4. The cobalt-aluminum-titanium co-coated positive electrode material according to claim 1, characterized in that: The content of the Co element in the coating layer is greater than the content of the Al element in the coating layer, or, The ratio of the content of the Al element in the coating layer to the content of the Co element in the coating layer is 1 to 1.2, or, The content of the Al element in the coating layer is 300 ppm to 600 ppm more than the content of the Co element in the coating layer.
5. The cobalt-aluminum-titanium co-coated positive electrode material according to any one of claims 1 to 4, characterized in that: In the coating layer, the Co element, the Al element and the Ti element exist in the form of one or more compounds, and the total mass of the compounds accounts for more than 80% of the total mass of the coating layer.
6. A method for preparing a cobalt-aluminum-titanium co-coated positive electrode material as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Mixing nickel-cobalt hydroxide, a doping source and a lithium source and sintering them to obtain a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material; Wherein, the doping elements in the doping source include Al element and A element, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti; (2) mixing a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a coating material and sintering the mixture to obtain the cobalt-aluminum-titanium co-coated positive electrode material; Wherein, the coating material includes Co source, Al source and Ti source; In step (1), the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05; In step (1), the sintering temperature is 400°C to 1000°C.
7. The preparation method according to claim 6, characterized in that: In step (2), the Co source includes at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide; and / or, In step (2), the Al source includes at least one of aluminum oxide, aluminum hydroxide and aluminum oxyhydroxide; and / or, In step (2), the Ti source is titanium oxide; and / or, The titanium oxide comprises at least one of titanium dioxide, titanium monoxide, titanium trioxide and titanium tetraoxide; and / or, In step (2), the sintering temperature is 350°C to 800°C; and / or, In step (2), the sintering time is 8h~24h; and / or, In step (2), after the sintering is completed, the temperature is cooled at a cooling rate of 0.01°C / min to 3°C / min.
8. The preparation method according to claim 6, characterized in that: The method further comprises: washing the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material prepared in step (1) with water, and then mixing it with a Co source, an Al source and a Ti source and sintering it to prepare a cobalt-aluminum-titanium co-coated positive electrode material.
9. The preparation method according to claim 6, characterized in that: Step (2) comprises: mixing a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material with a portion of a coating material and performing a primary sintering, washing the product of the primary sintering, and then mixing it with another portion of the coating material and performing a secondary sintering to obtain the cobalt-aluminum-titanium co-coated positive electrode material; and / or, The temperatures of the primary sintering and the secondary sintering are independently 350° C. to 800° C.; and / or, The total time of the primary sintering and the secondary sintering is 8h~24h.
10. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The positive electrode comprises the cobalt-aluminum-titanium co-coated positive electrode material as described in any one of claims 1-5.
Citation Information
Patent Citations
Titanium-doped high-nickel ternary lithium ion battery positive electrode material and preparation method thereof
CN113130901A
Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
CN116632240A
Lithium nickel cobalt aluminate positive electrode material, preparation method thereof and lithium ion battery
CN118117050A
Positive electrode material and preparation method and application thereof
CN118352508A
Positive electrode material, preparation method thereof, positive electrode plate and electrochemical device
CN118738368A